Educating International Students about Rabies through the Kansas State University Rabies Laboratory: A Field Experience Report - Noviyanti (My University, 2018)
This report presents a detailed field experience undertaken for 180 hours with the Kansas State University Rabies Laboratory. The agency is the primary diagnostic lab for the state of Kansas (and until recently, Nebraska). In addition, the lab provides support for the teaching and research responsibilities of the Department of Diagnostic Medicine/Pathobiology, the College of Veterinary Medicine and Kansas State University. Rabies is a deadly zoonosis endemic in the United States, including in Kansas. Animal control programs emphasize in vaccination of dogs and cats, and removal of stray animals have been essential in reducing the risk of rabies exposures to humans. Bats are also a potential reservoir of rabies for humans. The Kansas State University Rabies Laboratory have received reports that bats sometimes enter the campus buildings, which in this case show that there are some possibilities that students can be exposed to the potential rabid wild animals. While most of human bite cases worldwide are due to dogs, more than 90% of animal cases in the U.S. occur in wildlife. This field experience focused on educating the international students about the risk of rabies transmission from wild animals because, as non-permanent residents in the U.S., they might never come across information about rabies in the United States. Developing a health campaign based on the target audience’s preference has strengthened my skill to strategically and effectively educate the public.
Keywords: rabies